ORGANIZATION OF FIRST-LINE LIFE SUPPORT FOR THE AFFECTED POPULATION IN AREAS WHERE EMERGENCY SITUATIONS HAVE OCCURRED - Kurbanova Nilufar Ravshanbekovna (Journal of new century innovations, 2023)
Abstract: Protection of the population and territories from emergency situations - a set of measures, methods, system of tools, efforts to prevent emergency situations and eliminate them. In this article, measures to relocate the population in the event of an emergency, evacuation of the population, life support measures.